Neutrophils in inflammatory bowel disease: disease-promoting versus protective functions - Yu, Shaochen; Zhang, Mengjie; Niu, Wenlu; Huang, Yuting; Dou, Ziyue; Tian, Beibei; Yang, Langlang; Lu, Jian (Frontiers in Immunology, 2026)
Inflammatory bowel disease (IBD) is a complex chronic intestinal inflammatory disorder whose pathogenesis involves aberrant interactions between genetic, environmental, microbial, and immune factors. Neutrophils, as key effector cells of innate immunity, are among the first immune cells to infiltrate the inflamed mucosa in IBD, and their role in the disease course is multifaceted. This review systematically elaborates on the dual functions of neutrophils in IBD. On one hand, activated neutrophils act as crucial “destroyers” promoting the initiation and progression of IBD by releasing effector molecules such as reactive oxygen species (ROS), proteases, and neutrophil extracellular traps (NETs), which disrupt the intestinal epithelial barrier, amplify the inflammatory cascade, promote thrombosis, and mediate resistance to corticosteroids and biologics. On the other hand, neutrophils also play key protective roles by efficiently clearing pathogens and apoptotic cells, secreting pro-angiogenic and tissue repair factors, modulating the stem cell microenvironment, and maintaining microbial homeostasis, thereby actively promoting mucosal healing and inflammation resolution. This article also delves into neutrophil heterogeneity, functional plasticity, and their complex interactions with the microbiota, and proposes new precision therapeutic strategies targeting neutrophils. A comprehensive understanding of the dynamic balance and regulatory mechanisms of this “dual-role guardian” will provide new perspectives for researching IBD pathogenesis and innovating treatments.